2007
DOI: 10.1111/j.1365-2710.2007.00858.x
|View full text |Cite
|
Sign up to set email alerts
|

Should TPMT genotype and activity be used to monitor 6-mercaptopurine treatment in children with acute lymphoblastic leukaemia?

Abstract: Genotyping at diagnosis identifies patients with a homozygous mutant TPMT and may prevent severe and life-threatening toxicity. ALL treatment monitoring should preferentially be based on repeated determinations of intracellular active metabolites (6-TGN) and methylated metabolites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
18
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 23 publications
4
18
0
Order By: Relevance
“…At disease diagnosis TPMT activities are much reduced and are not reflective of on-therapy activities. This reduction has been previously reported [26], along with the resulting TPMT genotypephenotype discordance, in small patient cohorts with low numbers of variant alleles [30,31], and is now confirmed in a large population of children with ALL. The reduction in TPMT activities is well below the ranges recorded for healthy children [15,30] and has been attributed to the Table 5 Thiopurine metabolism in the year 1 and in the end of year 2 assays.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…At disease diagnosis TPMT activities are much reduced and are not reflective of on-therapy activities. This reduction has been previously reported [26], along with the resulting TPMT genotypephenotype discordance, in small patient cohorts with low numbers of variant alleles [30,31], and is now confirmed in a large population of children with ALL. The reduction in TPMT activities is well below the ranges recorded for healthy children [15,30] and has been attributed to the Table 5 Thiopurine metabolism in the year 1 and in the end of year 2 assays.…”
Section: Discussionsupporting
confidence: 75%
“…Sequencing revealed only two rare and three novel TPMT alleles. This discordance in the intermediate activity range has previously been reported in small patient cohorts and healthy subjects [19,31,38]. The first large scale TPMT genotype-phenotype concordance study in healthy blood donors (n = 1214) reported a clearly defined trimodal distribution and an overall concordance of >98% yet, after sequencing all discordant samples, reported 13 of 111 (11.7%) individuals with an intermediate activity wild-type in the open-reading frame [19].…”
Section: Discussionsupporting
confidence: 56%
“…4,9 Genotyping seems to be an important strategy for the prospective detection of deficiencies in TPMT activity, thus making it possible to provide adequate and individualized doses of 6-MP, minimizing the risks of toxicity 36,37 while maintaining efficacy in the treatment. 32 Differences in survival for patients with the homozygous wild-type and the heterozygous genotype have not been demonstrated, but preliminary data indicate that minimal residual disease positivity on day 78 of treatment is significantly lower in heterozygotes than in patients with homozygous wild-type alleles.…”
Section: Discussionmentioning
confidence: 99%
“…It is noteworthy to mention that not all cases of myelosupression are due to a mutation in the gene coding for the TPMT enzyme and therefore, not all cases can be prevented by screening for TPMT with either the enzymatic assay or genotype test [20]. The presence of toxicity in a number of cases and the lack of common types of mutations may result from the existence of other alleles, multigeneic contribution or other nongenetic factors [21]. Measurement of active 6-MP metabolite concentrations was suggested to be a key tool complementary to genotype in predicting toxicity under treatment with thiopurines [3].…”
Section: Discussionmentioning
confidence: 99%